High-Fidelity Microsurgical Simulation: The Thiel Cadaveric Nerve Model and Evaluation Instrument. Issue 4 (November 2019) - Odobescu, Andrei; Dawson, Deborah; Goodwin, Isak; Harris, Patrick G.; BouMerhi, Joseph; Danino, Michel A.
With surgical education moving from a time-based to a competency-based model, developing high-fidelity simulation models has become a priority. The Thiel cadaveric model has previously been used for a number of medical and surgical simulations, including microvascular simulation. We aim to investigate the use of the Thiel model in peripheral nerve simulation and validate a novel evaluation instrument. Sixteen residents ranging from postgraduate years 1 to 6 participated in the study. Their nerve coaptations using Thiel cadaveric nerves were video recorded and evaluated by 5 fellowship-trained microsurgeons using the Micro-Neurorrhaphy Evaluation Scale (MNES). The intraclass correlation among the 5 evaluators was 0.75, revealing excellent interrater reliability. The Cronbach α was .77, underlining the internal consistency of the test items. Bivariate analysis revealed a significant association between the MNES scores and the participants' self-declared level of experience. This correlation was confirmed by mixed modeling. Our results validate the MNES and underscore the utility of the Thiel nerve tissue for peripheral nerve surgical simulation.